Data analysis of entropy generation in quadratic radiative with chemically reactive Williamson fluid flow past an inclined porous sheet - Md. Yousuf Ali; Mizanur Rahman; Md. Shakib Hossain; Mst. Sharmin Akter; Noor Muhammad; Atia Sanjida Talukder (Partial Differential Equations in Applied Mathematics)
Data analysis (DA) is crucial in materials science and engineering for optimizing heat and mass transport processes. This study investigates the impact of magneto-hydrodynamics (MHD), quadratic radiation, and chemical reactions on entropy generation in Williamson fluid over an inclined porous sheet (IPS). It uses a numerical approach that integrates the 6th-order Runge-Kutta (R-K) method with the Nachtsheim-Swigert (N-S) shooting technique after transforming the governing equations into ordinary differential equations (ODEs). The research aims to elucidate the entropy generation dynamics of the Williamson fluid, examining the effects of quadratic radiative MHD chemical reactions. The key novelty of this work is that for 0.5 ≤ Kr ≤ 2.5, entropy production increases by 90.09% with linear radiation and by 114.60% with quadratic radiation, with the increase being higher for quadratic radiation. However, entropy generation for quadratic radiation is 14.10% lower than for linear radiation at Kr = 0.5. For an inclined sheet, it is 8.14% less than for a flat sheet at K = 2.5, and for Williamson fluid, it is 3.76% less than for Newtonian fluid at a diffusion coefficient of ϑ = 1.0. Additionally, the temperature increases in both the linear as well as quadratic radiation situations when the Williamson and radiation parameters increase. Regression analysis confirms the model's durability and accuracy at a 95% confidence level, with an R2 value of 99.92% and a strong positive correlation of over 99% between chemical processes and entropy creation. Understanding entropy production is crucial for optimizing cooling systems and heat exchangers, including biotechnology.